Statement by Professor Michał Heller at the Templeton Prize news conference, March 12th, 2008 - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
Reprint form <http://www.templeton.org/>.